Revealing optical vortices with a small number of photons. Issue 1 (28th November 2016) - Zhang, Wuhong; Wang, Jikang; Li, Fangshu; Chen, Lixiang; Karimi, Ebrahim
Abstract : Detecting vortices hidden in an ultra‐weak light fields is usually difficult. Zhang et al. present a high‐efficiency scheme to illuminate and reveal these optical vortices with only a small number of photons. Their method is based on the development of spiral phase filtering technique with high‐order vortex phase plates to visualize both topological charges and locations of the vortices. This work may find potential application in astronomical optics and biosensing. Abstract: Detecting the optical vortices of darkness hidden in an ultra‐weak background is a difficult task. Here we report an experiment demonstrating that the optical vortices can be directly visualized and identified with a smaller number of photons. Our method is based on the extension of the spiral phase contrast technique to incorporate vortex phase plates (VPP) of high‐order topological charges. In our experiment, we prepare optical vortex arrays of interesting structures such as Arabic numerals and the wings carrying various topological charges. By placing various VPP filters in the Fourier plane of a 4f imaging system, the embedded vortices of an incident ultra‐weak light field can be visualized, revealing both their positions and topological charges. It is found that a higher order vortex generally requires a smaller number of photons to be detected. Our method may find potential application in the fields of astronomical optics and biosensing in an ultra‐weak light environment.